2020
DOI: 10.1111/jonm.12947
|View full text |Cite
|
Sign up to set email alerts
|

The impact of work environment on workplace violence, burnout and work attitudes for hospital nurses: A structural equation modelling analysis

Abstract: Aim We aimed to test a model examining the direct and indirect effects of the work environment on workplace violence, nurse burnout and work attitudes of Chinese hospital nurses. Background Work environment is a key factor related to nurses' work attitudes. There has been limited information about how the work environment influences nurses' work attitudes. Method This was a cross‐sectional study that included 1,517 hospital nurses in 111 medical/surgical units in 23 hospitals from Guangdong province, China. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 29 publications
4
52
0
1
Order By: Relevance
“…In case of the relationship of perceptions of the work environment→job burnout model, the results in this study are in accord with two China's studies (Qian et al, 2020;Wu et al, 2020) and a study in the western country (Jameson & Bowen, 2018). Similarly, multiple studies indicate abusive supervision (Wu & Hu, 2009), organizational injustice (Manville et al, 2016), quality of the employee-manager relationship (Medler-Liraz & Seger-Guttmann, 2017), changing job characteristics (Bernhard-Oettel et al, 2018), and employees' work reflection (Walter & Haun, 2020) initiates emotional exhaustion.…”
Section: Discussionsupporting
confidence: 81%
“…In case of the relationship of perceptions of the work environment→job burnout model, the results in this study are in accord with two China's studies (Qian et al, 2020;Wu et al, 2020) and a study in the western country (Jameson & Bowen, 2018). Similarly, multiple studies indicate abusive supervision (Wu & Hu, 2009), organizational injustice (Manville et al, 2016), quality of the employee-manager relationship (Medler-Liraz & Seger-Guttmann, 2017), changing job characteristics (Bernhard-Oettel et al, 2018), and employees' work reflection (Walter & Haun, 2020) initiates emotional exhaustion.…”
Section: Discussionsupporting
confidence: 81%
“…Conversely, a nurse work environment rated as poor was implicated in decreased nurse work performance, increased turnover intention and reduced job satisfaction (Al Sabei et al, 2020;Wu et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Burnout is regarded as one of the relevant consequences of WPV [2,25]. Associations between WPV and burnout, turnover intention [26,27], and intention to leave [28] have been described.Secondary traumatic stress (STS) is a syndrome including intrusion, avoidance, and arousal resulting from indirect traumatic exposure in a professional context [29]. A study conducted in Israel showed that psychiatric nurses reported higher levels of STS symptoms compared to community nurses [30].…”
mentioning
confidence: 99%
“…Burnout is regarded as one of the relevant consequences of WPV [2,25]. Associations between WPV and burnout, turnover intention [26,27], and intention to leave [28] have been described.…”
mentioning
confidence: 99%